2015
DOI: 10.1016/j.scr.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostatic pressure promotes the proliferation and osteogenic/chondrogenic differentiation of mesenchymal stem cells: The roles of RhoA and Rac1

Abstract: Our previous studies have shown that hydrostatic pressure can serve as an active regulator for bone marrow mesenchymal stem cells (BMSCs). The current work further investigates the roles of cytoskeletal regulatory proteins Ras homolog gene family member A (RhoA) and Ras-related C3 botulinum toxin substrate 1 (Rac1) in hydrostatic pressure-related effects on BMSCs. Flow cytometry assays showed that the hydrostatic pressure promoted cell cycle initiation in a RhoA- and Rac1-dependent manner. Furthermore, fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 70 publications
3
73
0
Order By: Relevance
“…In addition, higher metabolic actives were observed for all cell culture formats subjected to mechanical stimulation, suggesting that IHP enhanced cell proliferation. This observation is in agreement with literature 38, 39. Hydrostatic pressure was found to enhance the proliferation of BMSC through the activation of the cell cycle and further studies have shown that hydrostatic pressure‐promoted cell cycle initiation greatly influenced by RhoA and Rac1 signaling 38, 39.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, higher metabolic actives were observed for all cell culture formats subjected to mechanical stimulation, suggesting that IHP enhanced cell proliferation. This observation is in agreement with literature 38, 39. Hydrostatic pressure was found to enhance the proliferation of BMSC through the activation of the cell cycle and further studies have shown that hydrostatic pressure‐promoted cell cycle initiation greatly influenced by RhoA and Rac1 signaling 38, 39.…”
Section: Discussionsupporting
confidence: 92%
“…This observation is in agreement with literature 38, 39. Hydrostatic pressure was found to enhance the proliferation of BMSC through the activation of the cell cycle and further studies have shown that hydrostatic pressure‐promoted cell cycle initiation greatly influenced by RhoA and Rac1 signaling 38, 39. SEM, EDX analysis, and positive alizarin red stain indicated calcium deposition on aligned and random fibers as well as TCP in static and dynamic culture.…”
Section: Discussionsupporting
confidence: 90%
“…Since it is known that mechanical stress, including hydrostatic pressure, stimulates Rho/ROCK signaling pathways 9 , we investigated the involvement of the Rho/ROCK pathway in PHP-induced stress fiber formation and FN fibrillogenesis using a Rho kinase inhibitor C3 and a ROCK inhibitor Y27632. Preincubation of hUASMCs with C3 or Y27632 significantly attenuated PHP (110–180 kPa, 0.002 Hz, 24 h)-induced stress fiber formation and FN fibrillogenesis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we demonstrated that PHP induced actin stress fiber formation and FN fibrillogenesis via Rho/ROCK pathways. Hydrostatic pressure-induced stress fiber formation has been reported in other cell types, including bone marrow mesenchymal stem cells 9, 34 , synovial fibroblasts 35 , and aortic endothelial cells 36 . Activated RhoA, a ras-related GTP-binding protein, is recognized to stimulate the appearance of stress fibers through the enhancement of cell contractility 37, 38 .…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, Wang et al [16] reported that bone morphogenic protein (BMP) promotes human mesenchymal stem cell (MSC) osteogenesis by altering cytoskeleton via activation of RhoA/ROCK signaling. Other studies showed that osteogenic growth peptide (OGP) [17], connective tissue growth factor [18], extracellular matrix [19], and hydrostatic pressure [20] promote the osteogenic differentiation of human bone marrow MSC (BMSC) via RhoA/ROCK signaling activation.…”
Section: Introductionmentioning
confidence: 99%